Treatment of dredged marine sediments for their Reuse in road construction. Traitement des sédiments de dragage marins en vue de leur réutilisation en techniques routières - BenAbdelghani, Farouk; Maherezi, W. (Science des matériaux (Laboratoire LARHYSS); Vol. 7 (2016): Science des matériaux (Laboratoire LARHYSS) Octobre, 2016)
great quantity of marine sand and sediments are dredged each year in Europe. Dredged sediments were considered as a waste product of the dredging operations and were a serious problem for the harbour managers. Recently, sediments are seen as a natural resource that could provides opportunities for a number of beneficial uses. However, these raw material can't be used in road construction without a specific treatment process. Sediments suitablity tests has shown that most of studied sediments are not suitable to be used in road construction. In order to improve theircompacity and their mechanical performance, addition of a granular material is recommended.The use of a dredged sand, to improve the granular mixture containing sediments, allows a better management of the two types of dredge materials (sand and sediment). In this study, a new road material containing dredged marine sediments and dredged sand is formulated and treated by adding various binders. Mechanical performance investigation of different mixtures by measuring Proctor-IPI values and simple compressive strengths is realized.